A Discussion of the Effect of Musical Context on Perception of Succession of Musical Events, and its Relevance for Philosophical Models of Temporal Experience - Phillips, Michelle Elizabeth (Empirical Musicology Review, 2015)
The article reviewed in this commentary takes philosophical models of temporal experience as its starting point, in an exploration of how an "experience of succession" may be distinguished from a mere "succession of experience". It is proposed that context is the important factor in differentiating the two experiences, rather than duration. Context is accounted for in broad terms, with specific discussion of gesture, performance environment, and mental imagery. The discussion may usefully pave the way for future collaboration between philosophers and psychologists. However, there are multiple fundamental findings in music cognition research, vital to any consideration of the context in which musical experiences occur (e.g. meter, tonality, expectation, familiarity), that could be factored into this discussion. The ideas discussed could be developed with greater consideration of recent empirical studies in music perception. Perhaps then a theoretical model of the experience of succession of musical events could give rise to experimental hypotheses, which may then be tested in order to further refine such models.